Resep Sukses UMKM Kuliner: Inovasi dan Higienitas dalam Satu Pelatihan - Aletta Dewi Maria TH; Ray Octafian; Elna Matasari Halawa; Dorotea Sotizunidar Waruwu (Nusantara Mengabdi Kepada Negeri, 2025)
Culinary micro, small, and medium enterprises (MSMEs) in Banjarnegara face significant challenges in managing innovations and implementing adequate hygiene standards. The limited knowledge and skills of MSME actors in these two aspects have an impact on low competitiveness and business sustainability in the midst of increasingly fierce market competition. This community service program aims to increase the capacity of culinary MSMEs through innovation management training and the implementation of hygiene standards. The program methodology includes a series of workshops, training sessions, and hands-on mentoring that are designed in a participatory and contextual manner according to local needs. The training material is comprehensively arranged, covering theoretical and practical aspects relevant to the characteristics of culinary MSMEs in Banjarnegara. The results of the program implementation showed a significant increase in participants' understanding of the importance of product innovation and the implementation of hygiene standards. The real impact of this program can be seen in improving product quality and variety, production process efficiency, and increasing revenue by 30-50% within six months after training. In addition, there has been a change in business behavior that is more adaptive and sustainability-oriented. The success of this program confirms the importance of a structured and participatory approach in empowering MSMEs, and shows that interventions based on local needs can produce significant economic and social impacts. The implementation model of this program has the potential to be replicated for the development of MSMEs in other sectors and regions with appropriate contextual adjustments.